AB0099 Expression Of GM-CSF and its Receptor CD116 in the Synovium of OA Patients is Negatively Correlated with Pain. (9th June 2015) - Pustjens, M.F.; Mastbergen, S.C.; Eijkelkamp, N.; Lafeber, F.P.
Abstract : Background: Pain is the most predominant symptom in osteoarthritis, however the underlying mechanisms are poorly understood. The synovium is a rich source of mediators that play a role in osteoarthritis and changes in synovitis have been associated with fluctuation of knee pain. In rodent models of rheumatoid arthritis and osteoarthritis the pro-inflammatory cytokine granulatocyte macrophage-colony stimulating factor (GM-CSF) has been identified as important mediator of inflammatory synovitis and pain [1, 2]. Objectives: This study evaluates the role of GM-CSF and its receptor CD116 in the synovium of osteoarthritis patients in relation to osteoarthritic pain. Methods: Synovial tissue was collected of end-stage knee osteoarthritis patients selected for total knee replacement surgery. Patients did not use medication in the year prior to surgery, except for occasionally acetaminophen. Expression of GM-CSF and CD116 in the synovial sublining, lining, or total area was analysed using frozen section immunohistochemistry. The level of pain experienced was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire and the Visual Analogue Scale (VAS). Histology and macroscopy of the synovium were scored (modified Goldenberg and Cohen score) and macroscopic synovial inflammation was graded (colour, angiogenesis, and fibrillation). Additionally, ex vivo TNFα, IL-1β, PGE2 and NO levels of the synovial tissue were measured. Results: GM-CSF expression in the synovial sublining and total synovial area was negatively correlated to the extent of knee pain (table 1 ). Similarly, CD116 expression was negatively correlated with pain in synovial sublining, lining and total area. Neither GM-CSF nor CD116 correlated with macroscopic or histologic inflammation scores. High levels of GM-CSF expression were correlated with low levels of TNFα, but no correlation was seen with IL-1β, PGE2 and NO levels. Conclusions: Higher levels of GM-CSF and CD116 expression in human synovial tissue is associated with lower levels of clinically observed knee pain in severe osteoarthritis patients. These findings contrast earlier studies showing pro-algesic effects of GM-CSF in an osteoarthritis animal model. Importantly, these findings highlight a potential role of GM-CSF in preventing pain in patients with OA. Clearly, more research is warranted before targeting GM-CSF in the synovium is a realistic option to improve pain in osteoarthritis. References: Cook AD, et al. Granulocyte-macrophage colony-stimulating factor is a key mediator in experimental osteoarthritis pain and disease development. Arthritis Res Ther 2012;14(5):R199. Cook AD, et al. Granulocyte-macrophage colony-stimulating factor is a key mediator in inflammatory and arthritic pain. Annals of the Rheumatic Diseases 2013;72(2):265-270. Acknowledgements: This study was funded by the Dutch Arthritis Association. Disclosure of Interest: None declared